Pengaruh Modal Kerja,Total Hutang,Tingkat Inflasi dan Penjualan Bersih Terhadap Laba Bersih - Nevin Wijaya; Veronika Veronika; Silvia Kosasih; Feby Natalia (Politeknik Ganesha Medan, 2021)
The purpose of this research is to examine and analyze the effect of working capital, total debt, inflation rate, and net sales on net income in retail trading companies listed on the Indonesia Stock Exchange 2015-2018 period. The research of this population was 27 retail trading companies listed on the IDX for the 2015-2018 period. With the purposive sampling technique, the number of research samples that meet the criteria is 9 companies, while the research method is descriptive quantitative research. The data collection method uses secondary data from financial reports while the data analysis model is multiple regression. The results of the F test research, namely working capital, total debt, inflation rate, and net sales have an effect on net income in retail trading companies listed on the Indonesia Stock Exchange in 2015-2018. Partially working capital has no effect on net income, partially total debt and inflation rate have a negative and significant effect on net income, while net sales have a positive and significant effect on net income. The coefficient of determination found R2 value of 0.313 (31.3%). The independent variable affects net income by 31.3% and the remaining 68.7% is affected by other variables. The conclusion from the results of this test is that of the 4 variables tested, there is 1 variable, namely working capital which does not affect net income.